A review of endoscopic ultrasound guided endoscopic retrograde cholangiopancreatography techniques in patients with surgically altered anatomy - Shah, Rucha Mehta; Tarnasky, Paul; Kedia, Prashant (Translational Gastroenterology and Hepatology, 2018)
Endoscopic retrograde cholangiopancreatography (ERCP) is the primary therapeutic intervention for pancreaticobiliary duct diseases. Surgically altered anatomy (SAA) makes performing successful ERCP challenging. In this review article the concept of endoscopic ultrasound guided pancreaticobiliary drainage (EUS-PBD) in cases of SAA where conventional ERCP fails or is not possible will be reviewed. EUS-PBD serves as an emerging and promising alternative for pancreaticobiliary therapy in the hands of skilled endoscopists compared to conventional therapies such as device-assisted ERCP, laparoscopic-assisted ERCP, or percutaneous drainage. The purpose of this review is to discuss the rationale, technique and current published outcomes on EUS-PBD for SAA.